Genital infections and local medications of complex use (application experiences) - E A Mezhevitinova; P R Abakarova; T V Brovkina; Sh M Poghosyan; Yu S Khlebkova (IP Berlin A.V., 2014)
Lower genital tract infections are one of the most frequent reasons for consulting the gynecologist (bacterial vaginosis - 30-35%, vulvovaginal candidiasis - 20-25%, mixed infections - 15-20%, trichomoniasis - 10%, other infections - 10%). Vulvovaginitis tends to grow regardless of the circumstances, is frequently recurrent, and difficult to treat. In the management of patients with different etiologies of vulvovaginitis it is crucial to choose the therapy method wisely. According to the requirements of the International Expert Council of the Centers for Disease Control and Prevention USA (CDC) when choosing the appropriate drug for treatment, it is recommended to take into account the need for drug effects on microbial associations, preferring the means of the elimination of a wide spectrum of possible pathogens that has both trichomonacistic, bactericidal, fungicidal and inflammatory effects. One of the preparations that meets such requirements, is a combined preparation of local action Neo-Penotran Forte L.